Chemically synthesized hydrogen fuel from reaction of methylcyclohexane over nanoporous heterogeneous catalysts. Issue 13 (7th June 2022) - Chasib, Khalid Farhod
ABSTRACT: Nanoporous oxides have been prepared, as hosts for the encapsulation of metal nanoparticles, and tested for the catalytic decomposition of methylcyclohexane (MCH) to produce hydrogen gas as a potential fuel source. The aim of the work is to test a range of mixed metal nanoparticle catalysts in the MCH to hydrogen reaction. The work investigates the use of a range of inexpensive metals in conjunction with traditional precious metal e.g. Pt. The objectives of work are prepared nanoporous oxides, comprising MCM- and SBA- types using established methods. Encapsulated metal nanoparticles within the pores of nanoporous oxide. Catalysts have been characterized fully to confirm porosity, surface area, and nanoparticle dispersion. The activity of catalytic of the various nanoporous materials was determined in the MCH to hydrogen reaction, and kinetic models developed from the associated experimental findings. GRAPHICAL ABSTRACT: UF0001